The effect of democracy on energy efficiency in European countries. Issue 1 (1st January 2020) - Chou, Li-Chen; Zhang, Wan-Hao
Abstract: This study explores to what extent the development of democracy affects energy efficiency. This study applies database reference from Freedom House, Polity IV project, International Country Risk Guide (ICRG) and World Development Indicator (WDI) to analyze the relationship between the level of democracy and energy efficiency of 35 countries in Europe from 1990 to 2013. Controlling for manufacturing value-added, price level, and GDP per capita, we find a significant statistical correlation between the level of democracy and the level of energy efficiency in a country. Empirical findings show that a high level of democracy has a significant positive impact on the improvement of national energy efficiency. Further examinations which employ quantile regression estimates indicate that the positive impact of democratic consolidation is stronger when the country is at the stage of relatively low energy efficiency. Empirical research also demonstrates that the consolidation of democratic institutions and economic development has a positive influence on the awareness of environmental conservation, thereby improving the structure of energy consumption and further reinforce the enhancement of energy efficiency.